Maggot nutrition content in various growing media (vegetable, fruit, and food processing industry): fish flour substitution - E. B. Barus; Yunilas; U. Hasanah; N. Najwa (Talenta Publisher, 2022)
Vegetable, fruit, and food processing industrial waste has a low nutritional content. The quality of the nutritional content is improved by processing it through fermentation. The study was conducted experimentally using a completely randomized design (CRD) factorial pattern. There were two factors (3 x 3), namely Factor I various maggot growing media (D1 = mustard greens, cabbage, and cauliflower leaves, D2 = banana, pineapple, and papaya, D3 = coconut dregs, tofu dregs, and cassava waste ) and Factor II fermentation time (L1 = 2 days, L2 = 4 days and L3 = 6 days), with three replications. The parameters of this study consisted of the nutritional content of maggot in the form of water content, dry matter, crude protein, crude fiber, crude fat, and ash. The results showed that various maggot-growing media had a significant effect (P<0.05) on the ash content and a very significant effect (P<0.01) on crude protein. No significant effect (P>0.05) was found on moisture content, dry matter, crude fiber, and crude fat. The duration of fermentation of maggot growing media had a significant effect (P<0.05) on crude protein and crude fat but had no significant effect (P>0.05) on moisture content, dry matter, ash content, and crude fiber. There was an interaction between various types of waste and the duration of fermentation of the media on the protein content of maggot. Still, there was no interaction with the water content, dry matter, crude fiber, crude fat, and ash.